Molecular Biomarkers in Pneumonia: Therapeutic Potential of Traditional Plant Medicine - Tirsa Persila Awairaro; Diniwati Mukhtar; Dicky Budiman; Himmi Marsiati (Indonesian Journal of Global Health Research, 2025)
Pneumonia causes 2.56 million global deaths annually, with current therapies limited by antimicrobial resistance and adverse effects. Traditional medicinal plants offer multi-target potential through anti-inflammatory, antioxidant, and immunomodulatory mechanisms. This review synthesizes knowledge on molecular biomarkers in pneumonia pathogenesis and evaluates therapeutic potential of medicinal plants, particularly Coleus amboinicus. A comprehensive literature search was conducted across PubMed/MEDLINE, Scopus, and Web of Science covering publications from January 2000 to June 2025. Inclusion criteria encompassed studies investigating molecular biomarkers, pneumonia therapeutic pathways, or medicinal plants with respiratory therapeutic properties. Narrative synthesis was employed due to study heterogeneity. Of 1,247 articles identified, 10 studies met inclusion criteria and were utilized in the analysis. Key inflammatory biomarkers included IL-6, TNF-α, and IL-1β, increasing from 5.05 mg/dL (controls) to 25.30 mg/dL in bacterial pneumonia. Neutrophil extracellular trap (NET) formation emerged as a central mechanism (47.36% of protein targets). Coleus amboinicus demonstrated 139 bioactive compounds with broad-spectrum antimicrobial activity and antioxidant properties (DPPH EC₅₀ 32.67-152.8 µg/mL). Traditional medicinal plants, particularly Coleus amboinicus, modulate key molecular pathways in pneumonia through sophisticated multi-target mechanisms, supporting integration of biomarker-guided approaches in contemporary respiratory care.